2021
DOI: 10.1002/imhj.21906
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in attachment patterns of preterm infants born in a non‐Western country

Abstract: Unexpected early birth of an infant may affect the attachment formation of mother–child dyads. This longitudinal study aimed to explore mother–infant attachment patterns of very preterm (VPT) and preterm (PT) infants compared to their term‐born peers in a non‐Western country. Neurodevelopmental outcomes of infants, maternal anxiety and depressive symptoms, and sociodemographic features were evaluated to explore their effects on attachment. Eighteen VPT, 11 PT, 11 term infants and their mothers participated. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(57 reference statements)
0
2
2
Order By: Relevance
“…Our results differ from the reported higher frequencies of avoidant (Fuertes et al, 2022) and disorganized attachment style (Wolke et al, 2014), and disorganized attachment scores (Zengin Akkus et al, 2021) in preterm infants compared to term infants from 12 months of age. Since we explored attachment at nine months, our data could suggest that any impact of prematurity on attachment takes longer to manifest.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results differ from the reported higher frequencies of avoidant (Fuertes et al, 2022) and disorganized attachment style (Wolke et al, 2014), and disorganized attachment scores (Zengin Akkus et al, 2021) in preterm infants compared to term infants from 12 months of age. Since we explored attachment at nine months, our data could suggest that any impact of prematurity on attachment takes longer to manifest.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results do not support the reported higher frequencies of disorganized attachment style (Wolke et al, 2014), and disorganized attachment scores (Zengin Akkus et al, 2021) in preterm infants compared to term infants from 12 months of age. Additionally, more insecure resistant attachment (López-Maestro et al, 2017, Sierra-García et al, 2018) and anxious attachment scores (Zengin Akkus et al, 2021) have been found in preterm infants at 18 months of age, whereas only three infants were assigned a resistant attachment style in this study. Interestingly, most studies using the Strange Situation Procedure show that approximately two thirds of preterm infants are assigned a secure attachment style from 12 months of age (Korja et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis by Korja et al (2012) on the attachment style of children born preterm has found that these children do not present more insecure attachment patterns (evaluated around one year of age) than children born full-term, in line with a recent review by Genet and Devouche (2022) . Nevertheless, a high risk of perinatal complications and developmental delays in the child can contribute to the development of an insecure attachment style ( Laganière et al, 2003 ; Brisch et al, 2005 ; Udry-Jørgensen et al, 2011 ; Korja et al, 2012 ; Zengin Akkus et al, 2021 ). Most studies have also failed to consider the role of environmental influences when studying the relationship between birth status and infant attachment style, as pointed out by Laganière et al (2003) .…”
Section: Introductionmentioning
confidence: 99%